Tantangan dan Strategi Pengelolaan Sumber Daya Manusia Pada Lembaga Pendidikan - m.nur, Yusaini; Prakoso, Wahyu Adi; Sulastri3, Sulastri3 (azkiya, 2023)
This article discusses the challenges in managing human resources (HR) and HR management strategies in educational institutions. The term "Human Resources" refers to the management of workforce in the context of educational institutions and meeting the needs of employees. HR management involves planning, recruitment, development, performance management, compensation, and maintenance of human resources to achieve organizational goals. HR management in educational institutions has specific challenges, such as recruiting and retaining qualified staff, developing employees, improving teaching quality, managing diversity, and adapting to environmental changes. HR management strategies in educational institutions include identifying organizational/institutional needs, employee recruitment and selection, skill development, and creating an organizational culture that supports staff growth. The development and recruitment of quality HR become the main focus of HR management strategies. Educational institutions need to provide employee development programs through training and skill enhancement, as well as career development programs to motivate employees. In recruitment, educational institutions should understand the needs of the positions to be filled and utilize effective selection methods. By implementing good HR management strategies, educational institutions can create a productive work environment, improve teaching quality, and effectively achieve organizational goals.